CONTINUOUS TRAINING OF ENGINEERS FOR INNOVATIVE ECOMONY IN THE RESEARCH UNIVERSITY - V. G. IVANOV; F. T. SHAGEEVA; M. F. GALIKHANOV (Высшее образование в России, 2017)
The Russian Federation needs engineers to provide innovative economy. The project of continuous professional training of engineers was developed in Kazan National Research Technological University that is based on a new type university benefits: developed system of professional education; integration of education process and scientific research held in university laboratories and scientific centers; opportunities of network cooperation and international collaboration; implementation of modern educational technologies including e-learning. The project illustrated by “Processing Technology of Polymers and Composite Materials” training program is multi-level and has continuity in both content and competences to be developed. Promising part of this training is study placements of Ph.D. students and specialists that are based on network cooperation with universities and partner-companies.